Information Message Of Kindness On The Architecture Gate Of The Palace Solo - Ayub Muktiono (Publisher Cv. Inara, 2021)
Human life in the natural world could not live alone. To achieve the goal of living together, the man will always interact with each other in society. Communication and information to be very important in communicating. Communication in the community can be done both verbally and non-verbally. Communication in non-verbal considered more timeless than verbal communication. One of the non-verbal communication which is carried out by the public is in the form of a building. Solo is a work of architecture that has a message non-verbal information from the king to his people. One part of the building of the Palace Solo that has the message information is on the door of the gate of the Kori Apit. With the method of approach to the interpretation of the shape of the marks found on the door of the gate of the Kori Flank and linked with the culture of the people of Java, then obtained the meaning of the information message that is very wise of the king that is delivered to his people.